Analisis Efektivitas Edukasi Gizi Dengan Video Tiktok Terhadap Pengetahuan Dan Sikap Konsumsi Gula Pada Siswa Man 1 Kota Palu - Nur Fadillah; Nikmah Utami Dewi (Jurnal Bina Ilmu Cendekia, 2025)
Diabetes mellitus (DM) is a non-communicable disease characterized by chronic increase in blood sugar levels due to impaired insulin secretion or function. One of the main risk factors for type 2 DM is excessive consumption of foods and drinks high in added sugar. High sugar consumption patterns among adolescents are of concern due to increasing diabetes prevalence at young age. This study aimed to analyze the effectiveness of nutrition education using TikTok video media on knowledge and attitudes based on Transtheoretical Model theory regarding consumption of sweet foods and drinks among students at MAN 1 Palu City. The research design was quasi-experimental with pre-test post-test control group. A sample of 40 students was selected through purposive sampling, consisting of 20 students in experimental group receiving education through TikTok and 20 students in control group with instructional videos. Data were analyzed using paired sample t-test for within-group differences and independent sample t-test for between-group differences. Results showed significant differences in students' knowledge scores in both groups (p=0.000), but attitude scores did not show significant differences (p>0.05). Based on Transtheoretical Model theory, students' attitudes changed from contemplation stage to preparation stage. Gain Score indicated instructional videos were slightly superior to TikTok. TikTok-based nutrition education and instructional videos were effective in improving adolescents' knowledge towards sugar consumption.